Communicating in an eventful campaign: A case study of party press releases during the German federal election campaign 2021 - Christoph Ivanusch; Lisa Zehnter; Tobias Burst (Electoral Studies, 2023)
Party competition during the German federal election campaign 2021 was marked by major external events and remarkable shifts in poll ratings. Existing literature argues that parties adjust their communication to such changing contexts and proposes three strategies: parties can respond to other parties, voter concerns or external events. In addition, these salience strategies are potentially moderated by further factors (e.g., poll ratings). The dynamic setting of the German federal election campaign 2021 provides an ideal case to bring together and test the outlined theories. We train a state-of-the-art model (BERT) on labeled manifestos and apply it for cross-domain topic classification of party press releases. The analysis shows that the parties used press releases for different purposes during the campaign and adjusted their issue communication to other parties and external events, but not to voter concerns. The use of different salience strategies was thereby unaffected by poll trends. These findings emphasize the influence of contextual changes on election campaigns and add important evidence to prominent theories of party competition.
https://doi.org/10.7910/DVN/8TNASL
Keywords: 320; Party competition; Salience strategies; German federal election; Press releases; BERT